Functional food colloids: studying structure and interactions during digestion. (June 2022) - Hong, Linda; Salentinig, Stefan
Abstract : The rational design of advanced food products provides a competitive advantage over empirical approaches. Colloidal structures in food are responsible for the bioaccessibility of poorly water-soluble nutrients. They can tailor food parameters including mechanical properties, texture, shelf-life, release of loaded bioactive molecules, and trigger the interactions with the components of the digestive tract. However, the fundamental understanding of the correlation between colloidal structures and their interactions with the digestive system that is necessary for the comprehensive design of novel colloidal food materials is not yet well established. This contribution summarizes the recent progress in examining the structural fate of food materials in their digestive transit. We discuss the design and characterization of colloidal food materials, advanced in vitro digestion models to study their composition, structure and interactions during digestion, and highlight the dynamic interactions of food materials with components of the digestive tract.